Effects of moderate-intensity continuous training and high-intensity interval training on serum levels of Resistin, Chemerin and liver enzymes in Streptozotocin-Nicotinamide induced Type-2 diabetic rats - Mohammad, Parastesh (J Diabetes Metab Disord, 2019)
BACKGROUND: The aim of this study was to investigate the effects of of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) in serum resistin, chemerin, insulin, liver enzymes and lipid profiles levels. METHODS: 24 Wistar rats with mean weight of 200 ± 50 g were randomly assigned to non-diabetic rats (ND-Cnt), diabetic control (D-Cnt), diabetic training groups. The diabetic training group received 10 weeks of HIIT (D-HIIT) and MICT (D-MICT) following the induction of diabetes. Evaluating resistin, chemerin and insulin hormones levels through ELISA. FBS and liver enzyme levels were measured by biochemical kits. RESULTS: HIIT and MICT resulted in a significant decrease in resistin, chemerin and fasting blood glucose (P < 0.05) compared to the D-Cnt (P < 0.05). Serum values of FBS, lipid profiles and liver enzyme (P < 0.05) decreased significantly more in the HIIT group compared with the MICT group (P < 0.05). As well as, the resistin level positively and significantly associated with values of ALT and chemerin level positively and significantly associated with values of ALT, ALP and AST in all rat (P < 0.05). CONCLUSION: In general, our findings demonstrated that the HIIT leads to better improvements in serum liver enzyme levels, FBS and lipid profiles compared to MICT. HIIT therefore appears to be an important time-efficient treatment for treatment with type 2 diabetes rats.